Bimetallic Pt-Sn/gamma-alumina catalyst for highly selective liquid phase hydrogenation of diethyl succinate to gamma-butyrolactone - Vaidya, S. H.; Rode, C. V.; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Platinum-tin bimetallic catalyst on gamma-alumina support was prepared by impregnation method and was reduced by sodium borohydride at room temperature. XRD and XPS characterization revealed that platinum was reduced to Pt-0 while, tin was probably partially reduced to Sn2+ due to the low temperature reduction method and Sn-0 was completely absent, avoiding the formation of P-Sn alloy. Pt-Sn/gamma-alumina (Pt 1%, Sn 9%) thus prepared was found to give almost complete selectivity to gamma-butyrolactone in liquid phase hydrogenation of diethyl succinate. A plausible reaction pathway is proposed involving Pt-O-Sn state and high selectivity to GBL is due to the Lewis acidity of Sn2+/4+ (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bimetallic Pt-Sn catalyst; gamma-butyrolactone selectivity; liquid phase hydrogenation of diethyl maleate; XPS of Pt-Sn; XRD of Pt-Sn

Biphasic hydroformylation of 1,4-diacetoxy-2-butene: a kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 1,4-diacetoxy-2-butene was studied using a water-soluble Rh complex catalyst prepared in situ from [Rh(COD)Cl](2) complex and trisodium salt of tri-(m-sulfophenyl)phosphine (TPPTS) in a biphasic system. The sequence of addition of catalyst precursor, ligand, and reactant/solvent showed a significant effect on leaching of Rh from aqueous to organic phase, and hence, the procedure was optimized to develop a nonleaching and stable biphasic catalyst system. The only hydroformylation product (1,4-diacetoxy-2-formyl butane, DAFB) formed was found to deacetoxylate completely to 2-formyl-4-acetoxybutene (FAB), thus allowing a one-pot synthesis of FAB, an important intermediate for Vitamin A. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained, and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst concentration were studied in a stirred batch reactor over a temperature range of 338-358 K. The effect of aqueous phase holdup on the initial rate of hydroformylation and analysis of gas-liquid and liquid-liquid mass transfer effects were also investigated to identify the reaction rate data operating in a kinetic regime. A rate equation based on the known hydroformylation reaction mechanism was used to fit the experimental rate data and to evaluate kinetic parameters. The agreement between the model prediction and the experimental data was found to be excellent. The activation energy was calculated as 30.1 kJ/mol. The biphasic catalyst system reported here is not only efficient for catalyst-product separation but also provides a tandem synthesis of Vitamin A intermediate, FAB.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007